Relativistic collapse of the classical triple bond in the CBi − molecular ion - Deniz Kahraman; Jie Hui; Xin-Yu Zhang; Neil A. Ellis; Hyun Wook Choi; Kirk A. Peterson; Lai-Sheng Wang (Science, 2026)
The conventional framework for chemical bonding between main-group elements involves separate σ and π orbitals to describe multiple bonds. However, relativistic effects mix these orbitals in molecules containing heavy elements through spin–orbit coupling, leaving the total angular-momentum projection (ω) as the only good quantum number. Direct experimental evidence that relativistic effects change the σ-π bonding framework has remained elusive. Here, we probe the carbon-bismuth triple bond in the CBi − anion using high-resolution cryogenic photoelectron spectroscopy, coupled with relativistic four-component Dirac-Coulomb coupled-cluster calculations. Even though the CBi − anion is isovalent to the well-known CN − species, we demonstrate that the traditional σ + 2π triple-bond picture collapses into a pure π-like |ω| = 3/2 and two |ω| = 1/2 Kramers pairs containing substantial σ/π mixing.